PL-4 (CIP596131.4): an Improved Potato Haploid Inducer - Ordonez, B.; Santayana, M.; Aponte, M.; Henry, I.M.; Comai, L.; Eyzaguirre, R.; Lindqvist-Kreuze, H.; Bonierbale, Merideth W. (Springer, 2021)
Dihaploid production from elite tetraploid cultivars is key to both traditional and novel breeding approaches that seek to simplify potato genetics. For this purpose, efficient and widely compatible haploid inducers (HIs) are needed. We compared PL-4, a new HI developed at the International Potato Center, to known HIs IvP101 and IvP35. By pollination of elite tetraploid breeding lines, we showed that PL-4 performed significantly better and had a homogeneous response regardless of the genetic background of the pistillate parents, on the most important efficiency traits-number of dihaploids per 100 fruits and haploid induction rate. Moreover, PL-4 exhibited a reduced proportion of hybrid seeds, a convenient trait for efficient screening. In this context, we recommend PL-4 as an enhanced HI for the potato breeding community.